Factors affecting willingness in using Islamic microfinance products in Mauritania - Maouloud, Vatimetou Mokhtar; Kassim, Salina; Othman, Anwar Hasan Abdullah (Springer International Publishing, 2021)
This study aims to identify factors affecting willingness in using Islamic microfinance products in Mauritania. Based on the experience of the Islamic microfinance institution PROCAPEC-Nouakchott, the study tests the effect of social barriers, religiosity, debt-phobia in affecting usage among the respondents. As well as testing the moderator effect of gender on relationships in the model. The study uses cross-sectional design data which was gathered through a questionnaire from a sample of 381 beneficiaries of an Islamic microfinance institution (PROCAPEC). It uses Structural Equation Modeling (SEM) to determine the impact of the voluntary factors on the use of Islamic microfinance products. The study finds that social barriers have a significant effect on the use of Islamic products; however, religiosity and debt-phobia did not have any impact on the usage of Islamic microfinance products. Gender has a moderator effect on the relationship between social barriers and usage. Nonetheless, gender does not have a moderator effect on the relationship between debt-phobia and usage as well as religiosity and usage. The findings are useful for the policymakers and managers of Islamic microfinance to consider the suitability strategies of awareness to make people voluntarily patronize Islamic microfinance products.